The role of technology and screen media use in treatment outcomes of children participating in a digital mental health intervention: a retrospective analysis of Bend Health - Kelsey McAlister; Darian Lawrence-Sidebottom; Donna McCutchen; Monika Roots; Jennifer Huberty; Jennifer Huberty (Frontiers in Digital Health)
IntroductionDigital mental health interventions (DMHIs) show promise in improving children's mental health, but there is limited understanding of how technology and screen media influence treatment outcomes. The purpose of this study was to leverage retrospective data to explore the relationships of technology and screen media use with mental health symptoms among children participating in a pediatric DMHI.MethodsChildren ages 6–12 years who participated in a DMHI, Bend Health Inc, in the United States were included. Caregivers reported their child's screen media use and mental health symptoms every 30 days. Associations of screen media use with mental health symptoms were examined at baseline and throughout DMHI participation.ResultsNearly all children (98.0%) used screen media, with 58.3% exhibiting problematic use and 23.2% showing elevated use at baseline. Elevated screen media use was associated with more severe depressive (z = 2.19, P = .022) and anxiety symptoms (z = 2.36, P = .019) at baseline, though associations differed by type. Video streaming, internet use, and gaming were linked to inattention, hyperactivity, and oppositional behavior (P's < 0.05). While screen media use decreased for most children during care (93.1%), those with elevated use showed marginally greater improvements in anxiety (z = −1.87, P = .062) and inattention symptoms (z = −1.90, P = .058).DiscussionFindings suggest a nuanced interaction between technology use and DMHIs. Future research should explore the specific contexts of screen media use to optimize DMHI effectiveness and address the potential adverse effects of certain screen media activities.